Legal Disharmony Between Traditional Fiqh and Positive Law in The Case of Triple Divorce Outside the Court Among the Banjar Community - M. Anshari; Muhammad Nafi (PT. Global Pustaka Ilmiah, 2025)
This study aims to analyze the legal disharmony between traditional fiqh and positive law in Indonesia in the practice of triple divorce (ṭalaq tiga) carried out outside the court among the Banjar community. This issue arises due to the dualism of legal authority religious authority held by the ulama and state authority exercised through the religious court. The research method used is normative legal research (doctrinal research) with statutory, conceptual, and case approaches. The data consist of primary and secondary legal materials, such as laws, the Compilation of Islamic Law (KHI), fiqh literature, and previous research findings. The analysis is conducted qualitatively to interpret legal norms and compare them with the living social practices in society. The results show that the Banjar community, which predominantly follows the Shafi‘i school of thought, still strongly upholds traditional fiqh provisions that consider triple divorce valid religiously, even if conducted outside the court. Meanwhile, Indonesia’s positive law through Law Number 1 of 1974 and the Compilation of Islamic Law (KHI) requires that a divorce is only valid if carried out before a session of the religious court. This difference creates social conflict and legal uncertainty within the community. The study concludes that harmonization between Islamic law and state law is necessary to ensure that the implementation of law in society does not cause social unrest and continues to guarantee justice, legal certainty, and the welfare (maṣlaḥah) of the people.